Informing Cross Cultural Understanding Curriculum through Classroom Research - Ingrid Brita Mathew (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
A short survey consisting of two questions was given in the first week of a Cross-Cultural Understanding course.  The first probed for students' schemata for culture.  The second probed for their awareness of cultural differences, as found in compliment-response adjacency pairs in Indonesian and English. The answers were analyzed and conclusions drawn as to which elements of the curriculum were redundant for that particular class, or needed less attention, and which elements needed more time and focus. Most students' definitions of culture included behavior, specific place and identity. Few included beliefs, values or environment.  The curriculum was adapted to spend less class time on cultural behaviors. Instead, from the second lesson, behaviors and places were linked with cultural norms, rules, geography and history. The compliment responses showed that most students were aware of differences between Indonesian and English.   That concept therefore did not need to be taught. Instead the curriculum built on from this example to directly introduce the topics of conversational analysis and pragmatic failure. Later in the semester the cultural meanings and functions of different English and Indonesian responses to compliments were analyzed. Each CCU class brings a level of cultural and language awareness. The curriculum can be adapted to take this into account.